Can Entrepreneurial Initiative Blunt the Economic Inequality–Growth Curse? Evidence From 92 Countries. Issue 2 (February 2021) - Patel, Pankaj C.; Doh, Jonathan P.; Bagchi, Sutirtha
Despite the growing interest in understanding the effects of income inequality on economic growth, the influence of entrepreneurship-related institutional constraints on the inequality–growth association remains less understood. Drawing on an institutional constraints perspective in the context of startup entry regulation and credit constraints, we propose that under increasing income inequality, ease of startup or access to credit from the financial sector is positively associated with per capita economic growth. In a sample of 92 countries, robust to alternate specifications, we find support for our hypotheses. Our findings contribute to the debates about the income inequality–growth nexus and imply potential policy interventions in the form of lower startup regulations and domestic credit provision from the financial sector to enhance economic growth under increasing economic inequality.